Bioremediation of contaminated diesel and motor oil through the optimization of biosurfactant produced by Paenibacillus sp. D9 on waste canola oil. Issue 1 (2nd January 2020) - Jimoh, Abdullahi Adekilekun; Lin, Johnson
Abstract: The potential of the indigenously isolated biosurfactant producing organism, Paenibacillus sp. D9 to utilize waste frying oils (canola, sunflower, castor, and coconut) were investigated as alternate cheap substrates for synthesis of biosurfactant. This work aimed to study optimum parameters, functional properties, and applicability for bioremediation. Initial biosurfactant yield showed 2.11 g/L and 33.7 mN/m, a representative of low production. There was an improvement on maximum reduction in surface tension and biosurfactant yield of 31.2 mN/m and 5.31 g/L, respectively as the two quadratic models were adequate with regards to biosurfactant yield (R 2 = 0.9937) and surface tension (R 2 = 0.9862). The proficiency of biosurfactant when contrasted to a chemical surfactant bring about the degradation of 73.2% motor oil, 71.8% diesel (shaking condition), 63.3% motor oil, and 59.3% diesel (static condition) in a solid environment. In contrast, using an aqueous environment, there was bio-removal of 77.6% motor oil, 74.3% diesel (shaking condition), 62.2% motor oil, and 57.4% diesel (static condition) respectively. The response surface methodology tool was suitable in identifying the optimum conditions on low-cost substrates and the biosurfactant is capable for bioremediation of diesel and motor and from contaminated environment.